Long-term outcome of surgical revascularization in patients with reduced left ventricular ejection fraction—a population-based cohort study. (21st April 2022) - Brynjarsdottir, Helga B; Johnsen, Arni; Heimisdottir, Alexandra A; Heidarsdottir, Sunna Rún; Jeppsson, Anders; Sigurdsson, Martin I; Gudbjartsson, Tomas
Abstract: OBJECTIVES: Surgical revascularization is an established indication for patients with advanced coronary artery disease and reduced left ventricular ejection fraction (LVEF). Long-term outcomes for these patients are not well-defined. We studied the long-term outcomes of patients with ischaemic cardiomyopathy who underwent surgical revascularization in a well-defined nationwide cohort. MATERIALS AND METHODS: A retrospective study on 2005 patients that underwent isolated coronary artery bypass grafting in Iceland between 2000 and 2016. Patients were categorized into two groups based on their preoperative LVEF; LVEF ≤35% ( n  = 146, median LVEF 30%) and LVEF >35% ( n  = 1859, median LVEF 60%). Demographics and major adverse cardiac and cerebrovascular events were compared between groups along with cardiac-specific and overall survival. The median follow-up was 7.6 years. RESULTS: Demographics were similar in both groups regarding age, gender and most cardiovascular risk factors. However, patients with LVEF ≤35% more often had diabetes, renal insufficiency, chronic obstructive pulmonary disease and a previous history of myocardial infarction. Thirty-day mortality was 4 times higher (8% vs 2%, P  < 0.001) in the LVEF ≤35%-group compared to controls. Overall survival was significantly lower in the LVEF ≤35%-group compared to controls, at 1 year (87% vs. 98%, P < 0.001) and 5 years (69% vs. 91%, P < 0.001). In multivariable analysis LVEF ≤35% was linked to inferior survival with an adjusted hazard ratio of 2.0 (95%-CI 1.5 - 2.6, p<0.001). CONCLUSIONS: A good long-term outcome after coronary artery bypass grafting can be expected for patients with reduced LVEF, however, their survival is still significantly inferior to patients with normal ventricular function. Abstract : Heart failure with reduced left ventricular ejection fraction (LVEF) as a result of coronary atherosclerosis is a major health burden, with a prevalence that is estimated to increase over the next decades [1].